2021
DOI: 10.1111/fcp.12732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anesthetics on oncogenic signaling network: a review on propofol and isoflurane

Abstract: Propofol as an intravenous anesthetic and isoflurane as an inhalational/volatile anesthetic continue to be an important part of surgical anesthetic interventions worldwide. The impact of these anesthetics on tumor progression, immune modulation, and survival rates of cancer patients has been widely investigated. Although most of the preclinical studies have provided a beneficial effect of propofol over isoflurane or other volatile anesthetics, several investigations have shown contradictory results, which warr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…Given the above, the present study elucidated a dose‐dependent bidirectional pharmacological action involving multiple mechanisms, including angiogenesis, apoptosis, and tumor immunity [53] (Figure 8). Notably, partial nonsignificant results in high‐dose combined regimens indicate the primary mechanism of metronomic combination chemotherapy seems to change with the doses or combinations of antineoplastic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Given the above, the present study elucidated a dose‐dependent bidirectional pharmacological action involving multiple mechanisms, including angiogenesis, apoptosis, and tumor immunity [53] (Figure 8). Notably, partial nonsignificant results in high‐dose combined regimens indicate the primary mechanism of metronomic combination chemotherapy seems to change with the doses or combinations of antineoplastic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing cancer cell proliferation and inducing their apoptosis are key strategies to prevent tumor growth. Recent studies have shown that anesthetics not only play a role in analgesia and sedation but can also inhibit drug resistance of tumor cells and inhibit tumor progression ( Ishikawa et al, 2021 ; Jing et al, 2022 ; Saha et al, 2022 ). To obtain a safe and effective anesthetic intervention, we need to understand the mechanism of these anesthetics to prevent cancer recurrence and promote longer postoperative survival.…”
Section: Regulatory Function Of Anesthetics In Cancermentioning
confidence: 99%
“…The mechanisms of action involve several neurotransmitter receptors, especially the GABA A receptor, and is considered a distinct sedative drug with low toxicity and rapid onset and metabolization [ 15 ]. In addition, evidence indicates that propofol can potentialize the antitumor effect of chemotherapy drugs, and studies of its application as a synergistic drug are under investigation [ 16 , 17 ]. Old uses and the recent needs justify the recognition of this drug as an essential medicine by the WHO since 2013 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%